KESESUAIAN PEMANFAATAN KOMPUTER DI TAMAN KANAK-KANAK DENGAN KURIKULUM YANG BERLAKU - Muman Hendra Budimam; Edy Sjarif; Denny Setiawan (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2016)
This research is a study to uncover whether the use of computer for early childhood education is in the line with curriculum at the schools. A broader use of computer for early childhood education can be seen in some kindergartens especially those which are located in big cities. However there was no research on whether the education programs are suitable or not for early childhood ages. Therefore this research was conducted. Some teachers who are teaching computer or using computer for developing children’s development aspects were given questionnaires about the goal of using computer in their school, the interaction between the programs of the computer with the curriculum they used in their schools, availability of the programs in their schools and the way they taught their children with the computer. Then, two teachers were interviewed to deepen understanding about what they were doing with the computer in their class. The researchers also observed their class to see what was going on in their class. The entry data were tabulated and interpreted. The result showed that according to the teachers some programs of the computer are suitable and can be used for early childhood education while some of them are not. Therefore a careful selection is needed to determine which programs can be used. This condition existed because the programs are very limited in market and the teachers have to download them from internet. The researchers recommend that some teachers’ organizations like IGTKI and Himpaudi involve in organize the use of computer programs so the teachers help each other in providing good programs for their children at schools.